Knowledge translation in the healthcare sector. A structured literature review - Dal Mas, F.; Garcia-Perez, A.; Sousa, M.; Lopes da Costa, R.; Cobianchi, L. (The Electronic Journal of Knowledge Management, 2020)
Knowledge translation can be understood as the ability to translate concepts between different contexts by stakeholders who have different skills, aims, and even feelings in their relation to such concepts. Knowledge translation tools allow for the effective transfer of existing knowledge as well as the emergence of new knowledge of value to some or all of the stakeholders involved in the process. Knowledge translation is particularly challenging in healthcare and medicine, where different practitioners (e.g. physicians, biologists, engineers, researchers) and professionals need methodologies and tools to communicate and share knowledge among them and with patients in an effective manner. To better understand this phenomenon, we conducted a Structured Literature Review (SLR). The concepts knowledge, translation and either healthcare or medicine were used as search terms in the title, abstract or keywords on Scopus, which highlighted more than 2,000 contributions in the medical literature and only 22 in Business and Management. Our review of these documents revealed a need in the healthcare sector for better managerial and organisational practices to cope with the various challenges related to the sharing of knowledge among stakeholders. At the same time, the business and management communities appear to have made significant progress in addressing the same issues. We therefore decided to concentrate our analysis on the works published by the business and management community as a mean to highlight future research directions for the healthcare management sector. Thus, our research identifies areas of relevance which are currently underdeveloped, provides insights on both theoretical and empirical developments and offers a critique of the approaches, research frameworks and methods used, as well as emerging trends in these domains. Despite a lack of an agreed definition of the term Knowledge Translation, our findings highlight a growing interest in the topic, with most of thecontributions published after 2015. Scholars have approached the term from a variety of perspectives depending on the nature of the stakeholders of relevance to their studies. Whilst there does not seem to be a predominant framework, the literature reveals several tools and techniques that are effective in enhancing Knowledge Translation in different contexts.New research opportunities in this domain emerge in terms of underinvestigated areas within the healthcare sector.